2022
DOI: 10.1155/2022/6996134
|View full text |Cite|
|
Sign up to set email alerts
|

The Application of Artificial Intelligence in Football Risk Prediction

Abstract: Football is the most popular sports in the World, with an estimated global following of 4.0 billion fans worldwide. Football draws attention from people of various age groups. The result of the game only decides the performance of the team and individual players. The player has to train smarter to avoid a career-ending injury. Sports have also entered into the new era of artificial intelligence as any industry. Artificial intelligence (AI) in football acts like a teammate to the players and also plays the role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
0
2
0
1
Order By: Relevance
“…El big data actual de Internet se ha convertido gradualmente en un punto caliente del desarrollo social, y ha sido ampliamente utilizado en varias industrias y ha logrado buenos resultados (Wang & Anhouck, 2022). La validez y confiabilidad de un nuevo transductor de posición lineal de bajo costo para medir la velocidad propulsora media en los deportes (Lopez-Torres et al, 2022), aporta una aplicación a través de la inteligencia artificial que proporciona la predicción de riesgos en los deportes (Qiao, 2022).…”
Section: Introductionunclassified
“…El big data actual de Internet se ha convertido gradualmente en un punto caliente del desarrollo social, y ha sido ampliamente utilizado en varias industrias y ha logrado buenos resultados (Wang & Anhouck, 2022). La validez y confiabilidad de un nuevo transductor de posición lineal de bajo costo para medir la velocidad propulsora media en los deportes (Lopez-Torres et al, 2022), aporta una aplicación a través de la inteligencia artificial que proporciona la predicción de riesgos en los deportes (Qiao, 2022).…”
Section: Introductionunclassified
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%